Surface and Airborne Measurements of Organosulfur and Methanesulfonate Over the Western United States and Coastal Areas - Sorooshian, Armin (Journal of geophysical research. Atmospheres : JGR, 2015)
This study reports on ambient measurements of organosulfur (OS) and methanesulfonate (MSA) over the western United States and coastal areas. Particulate OS levels are highest in summertime, and generally increase as a function of sulfate (a precursor) and sodium (a marine tracer) with peak levels at coastal sites. The ratio of OS to total sulfur (TS) is also highest at coastal sites, with increasing values as a function of Normalized Difference Vegetation Index (NDVI) and the ratio of organic carbon to elemental carbon. Correlative analysis points to significant relationships between OS and biogenic emissions from marine and continental sources, factors that coincide with secondary production, and vanadium due to a suspected catalytic role. A major OS species, methanesulfonate (MSA), was examined with intensive field measurements and the resulting data support the case for vanadium's catalytic influence. Mass size distributions reveal a dominant MSA peak between aerodynamic diameters of 0.32-0.56 μm at a desert and coastal site with nearly all MSA mass (≥ 84%) in sub-micrometer sizes; MSA:non-sea salt sulfate ratios vary widely as a function of particle size and proximity to the ocean. Airborne data indicate that relative to the marine boundary layer, particulate MSA levels are enhanced in urban and agricultural areas, and also the free troposphere when impacted by biomass burning. Some combination of fires and marine-derived emissions leads to higher MSA levels than either source alone. Finally, MSA differences in cloud water and out-of-cloud aerosol are discussed